2015
DOI: 10.3390/ma8085252
|View full text |Cite
|
Sign up to set email alerts
|

Metal Nanoparticle-Decorated Two-Dimensional Molybdenum Sulfide for Plasmonic-Enhanced Polymer Photovoltaic Devices

Abstract: Atomically thin two-dimensional (2D) transition metal dichalcogenides have also attracted immense interest because they exhibit appealing electronic, optical and mechanical properties. In this work, we prepared gold nanoparticle-decorated molybdenum sulfide (AuNP@MoS2) through a simple spontaneous redox reaction. Transmission electron microscopy, UV-Vis spectroscopy, and Raman spectroscopy were used to characterize the properties of the AuNP@MoS2 nanomaterials. Then we employed such nanocomposites as the catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…Singha et al, 2015). There are other cases where doping has been successfully executed on MoS 2 but for such cases, when comparing the Raman spectra for the doped and the pristine MoS 2 , no significant change is observed (Laskar et al, 2014;Chuang et al, 2015). However, in our study, most of the expected results mentioned above were not observed upon applying p-type doping on MoS 2 using Au.…”
Section: Characterization Of Doped Moscontrasting
confidence: 45%
“…Singha et al, 2015). There are other cases where doping has been successfully executed on MoS 2 but for such cases, when comparing the Raman spectra for the doped and the pristine MoS 2 , no significant change is observed (Laskar et al, 2014;Chuang et al, 2015). However, in our study, most of the expected results mentioned above were not observed upon applying p-type doping on MoS 2 using Au.…”
Section: Characterization Of Doped Moscontrasting
confidence: 45%
“…MoS 2 in combination with MoO 3 and MoS 2 with Au nanoparticles were also used as hole extraction layers in organic solar cells by Qin et al [227] and Yang et al [228] respectively. Chuang et al [229] used nanosheets of MoS 2 along with Au nanoparticles as an electron extraction layer and obtained PCE of 4.91%.…”
Section: Mos 2 As a Diverse Role Materials In Organic Solar Cellsmentioning
confidence: 99%
“…An additional and appealing molecular strategy commonly used to functionalize solution-processed TMD nanosheets envisages the growth of noble metal nanoparticles (NPs), mainly Au, 126,127 Pd, 128,129 Pt 130,130 and AgNPs, 131,132 and their interactions with the 2D systems (Fig. 9).…”
Section: Defectsmentioning
confidence: 99%